ANALISA FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN MOTOR HONDA VARIO PADA CV. CITRA SENTOSA MANDIANGIN - Evvi Puspawaty . (Konsentrasi Manajemen Pemasaran Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2017)
This research focus on examinig factors that inluencing purchusing decion of Honda Vario vechile of CV. Citra Mandiangin Sentosa firms. Research method used survey to collect data and accompanied by obeservation techniques. Secondary data are collected form some related institutions. Based on the results, product variations, quality and desgin are atributes that consider analisis factor influencing purchasing decision. Keywords : Motor Honda Vario; Diversity Products; Product Quality; design, and Purchasing Decisions